High‐resolution 3D radial bSSFP with IDEAL. Issue 1 (15th March 2013) - Moran, Catherine J.; Brodsky, Ethan K.; Bancroft, Leah Henze; Reeder, Scott B.; Yu, Huanzhou; Kijowski, Richard; Engel, Dorothee; Block, Walter F.
<x xml:space="preserve">Abstract</x> Radial trajectories facilitate high‐resolution balanced steady state free precession (bSSFP) because the efficient gradients provide more time to extend the trajectory in k‐space. A number of radial bSSFP methods that support fat–water separation have been developed; however, most of these methods require an environment with limited B0 inhomogeneity. In this work, high‐resolution bSSFP with fat–water separation is achieved in more challenging B0 environments by combining a 3D radial trajectory with the IDEAL chemical species separation method. A method to maintain very high resolution within the timing constraints of bSSFP and IDEAL is described using a dual‐pass pulse sequence. The sampling of a unique set of radial lines at each echo time is investigated as a means to circumvent the longer scan time that IDEAL incurs as a multiecho acquisition. The manifestation of undersampling artifacts in this trajectory and their effect on chemical species separation are investigated in comparison to the case in which each echo samples the same set of radial lines. This new bSSFP method achieves 0.63 mm isotropic resolution in a 5‐min scan and is demonstrated in difficult in vivo imaging environments, including the breast and a knee with ACL reconstruction hardware at 1.5 T. Magn Reson Med 71:95–104, 2014. © 2013 Wiley Periodicals, Inc.